Recreational and ergogenic substance use and substance use disorders in elite athletes: a narrative review. Issue 12 (8th June 2019) - McDuff, David; Stull, Todd; Castaldelli-Maia, João Mauricio; Hitchcock, Mary E; Hainline, Brian; Reardon, Claudia L
Abstract : Background: Substances from various classes may be used for recreational purposes, self-treatment or to boost performance. When substance use shifts from occasional to regular, heavy or hazardous use, positive and negative effects can develop that vary by substance class and athlete. Regular use of recreational or performance enhancing substances can lead to misuse, sanctions or use disorders. Objective: To review the prevalence, patterns of use, risk factors, performance effects and types of intervention for all classes of recreational and performance enhancing substances in elite athletes by sport, ethnicity, country and gender. Methods: A comprehensive search was conducted to identify studies that compared the prevalence and patterns of substance use, misuse and use disorders in elite athletes with those of non-athletes and provided detailed demographic and sport variations in reasons for use, risk factors and performance effects for each main substance class. Results: Alcohol, cannabis, tobacco (nicotine) and prescribed opioids and stimulants are the most commonly used substances in elite athletes, but generally used at lower rates than in non-athletes. In contrast, use/misuse rates for binge alcohol, oral tobacco, non-prescription opioids and anabolic-androgenic steroids are higher among athletes than non-athletes, especially in power and collision sports. Cannabis/cannabinoids seem to have replaced nicotine as the second most commonly used substance. Conclusions: Substance use in elite athletes varies by country, ethnicity, gender, sport and competitive level. There are no studies on substance use disorder prevalence in elite male and female athletes and few studies with direct comparison groups.